Abiotic factors influencing the health of mature Araucaria heterophylla (Norfolk Island Pine trees) in urban coastal parks - Anna Petrova; Chris Pratt; Ruby Naomi Michael (Environmental Management, 2026)
Tree decline can significantly impact both the aesthetic value and ecological function of urban forests. Understanding the abiotic factors influencing tree health is essential for developing effective management strategies. This study investigated the decline of heritage Araucaria heterophylla (Norfolk Island Pine) in urban areas of the Gold Coast, Queensland, Australia, with a focus on identifying underlying abiotic causes. General assessment was conducted along a 5-km coastal strip (including 946 trees); climate conditions on the Gold Coast and Norfolk Island were compared; and 38 selected trees of varying health status were examined in detail. This included soil physicochemical and nutrient analysis, as well as foliar nutrient profiling. Results showed that 15.8% of the 946 initially assessed trees exhibited symptoms of decline, such as dieback, browning of foliage tips, extensive defoliation and shortened foliage length. Mean temperatures on the Gold Coast were consistently higher than those in the species’ native range and the current decline followed a period of elevated temperatures and reduced rainfall. Declining trees ( n = 32) from the subset population were found to be growing in compacted soils, with significantly elevated foliar sodium and lower foliar carbon levels compared to healthy trees ( n = 6), indicating possible disruption of nutrient regulation. Half of the trees in the advanced stage of decline were located less than 5 m away from carparks (50%), which was higher when compared with Moderate Decline (18.7%) and very healthy Benchmarking trees (0%). Most trees in the advanced decline category were not mulched and had turfgrass as the primary groundcover (62.5%), whereas trees in moderate decline were more commonly associated with turfgrass combined with fallen branchlets (43.75%). In addition, all Benchmarking trees were located in sandy soils, whereas declining trees were more commonly associated with loam soils, which are more susceptible to compaction. Key abiotic stressors identified were extreme weather and proximity to urban infrastructure. Management recommendations include improving root zone conditions by providing irrigation during dry periods, mulching, implementing routine health monitoring to support early intervention and, for new planting, increasing distances from hard infrastructure.

What Kills Mature Street and Park Trees in Cities? Systematic Quantitative Review of Published Case Studies - Anna Petrova; Ruby Naomi Michael; Chris Pratt (Environmental Management, 2025)
Street and park trees often endure harsher conditions, including increased temperatures and drier soil and air, than those found in urban or natural forests. These conditions can lead to shorter lifespans and a greater vulnerability to dieback. This literature review aimed to identify confirmed causes of street and park tree dieback in urban areas from around the world. Peer-reviewed case studies related to urban tree decline were scanned for the words “urban”, “city”, “cities”, “tree*”, “decline”, “dieback”, “mortality”, and “survival”. From an initial pool of 1281 papers on Web of Science and 1489 on Scopus, 65 original peer-reviewed research papers were selected for detailed analysis. Out of all species reported to decline, 46 were native, while non-natives were represented by 35 species. The most commonly affected trees were Platanus, Fraxinus, Acer, and Ficus . Most studies were conducted in Mediterranean, humid subtropical, and humid continental climates, with the greatest representation from the United States, followed by Australia, Brazil, Iran, Italy, and Russia. Many authors focused on either biotic or abiotic causes of dieback; some explored both, and some also discussed underlying environmental and urban stresses as potential predisposing factors. The majority (81% of the papers) concluded that a decline was caused by either an arthropod or a microorganism. Overall, it was suggested that changing management strategies to improve water availability and soil health might help with tree resilience. Additionally, regular monitoring and research, along with improving tree species selection and implementing biological and chemical control methods, can help prevent or slow down tree decline. Increasing awareness and adopting preventative approaches could help to extend the lifespan of street and park trees in urban environments and mitigate some of the biological threats, especially considering the challenges we may be facing due to the changing climate.

Manatee Mortality in Puerto Rico - Antonio A. Mignucci-Giannoni; Ruby A. Montoya-Ospina † , Nild (Environmental Management, 2000)